Influencia del estado nutricional e hidratación en el rendimiento físico de adolescentes futbolistas, Loreto 2024 - Fernández Ramírez, Adriana Elizabeth (2025)
This research analyzed the influence of nutritional status and hydration on the physical performance of 56 adolescent soccer players (12-17 years old) from Club Deportivo A.D. Bolognesi, Loreto 2024, through a cross-sectional quantitative-observational study. The evaluation included anthropometric parameters (BMI, body fat percentage, waist circumference), pre/post training urinary specific gravity, and physical performance (ALPHA-FITNESS battery). Results revealed that 82.14% presented normal BMI, although 66.1% showed low body fat percentage. Dehydration increased significantly during training (48.2% to 69.6%). In motor capacity, 60.8% reached high/very high levels, while only 41% exceeded the medium level in aerobic capacity. Significant negative correlations were identified between waist circumference and aerobic capacity (r=-0.452, p<0.001), and between urinary gravity and aerobic performance (r=0.321, p=0.008). The effects of hydration were substantial on both motor capacity (d=0.728) and aerobic capacity (d=1.681). It is concluded that both factors significantly influence performance, with waist circumference and hydration status being the most consistent predictors of aerobic performance. Amazonian conditions appear to intensify the impact of dehydration, suggesting the need for contextualized hydration strategies.